The Association between Aerobic Fitness and Congruency Sequence Effects in Preadolescent Children - Westfall, Daniel R. (Brain Cogn, 2017)
Aerobic fitness has previously been related to cognitive control in preadolescents; however, these investigations have generally relied on global measures of performance. Thus, we have little understanding of how aerobic fitness may relate to trial-by-trial modulations in cognitive control. This study utilized congruency sequence effects (CSEs), which characterize how behavior on the current trial is influenced by the previous trial, to investigate the relation of aerobic fitness on varying levels of cognitive control. One hundred eighty-seven children completed tests of aerobic fitness and a flanker task. Regressions were performed to determine relationships between CSE sequences and aerobic fitness while controlling for other potential confounding factors (e.g., age, sex, IQ). Lower-fit children were less able to modulate cognitive control during sequences requiring relatively less cognitive control. Additionally, lower-fit children were less able to adjust for variable levels of cognitive control during relatively more difficult sequences. Lastly, lower-fit children had longer reaction times (RTs) for all sequences in the condition requiring greater amounts of cognitive control. These findings corroborate the importance of aerobic fitness for cognitive control in school-aged children, and extend the literature by demonstrating a relationship between fitness and trial-by-trial modulations in control demands.